Unveiling Tax Avoidance: The Mediating Role of Sustainability Reporting Quality in Board Influence - Ezar, Abraham Romamti; Widianingsih, Luky Patricia (Forum Kerjasama Pendidikan Tinggi, 2026)
This study investigates the effect of board size on tax avoidance in Indonesian public companies, with sustainability reporting quality (SRQ) as a mediating variable. Using panel data from 48 energy sector firms listed on the Indonesia Stock Exchange from 2017 to 2023, multiple linear regression analysis is employed. Drawing on agency theory, this study examines whether board size enhances monitoring effectiveness and reduces information asymmetry, thereby constraining managerial tax behavior. The results show that board size does not have a significant direct effect on tax avoidance, indicating that governance structure alone is insufficient to influence complex tax decisions in capital-intensive industries. However, board size has a significant positive effect on sustainability reporting quality, suggesting stronger oversight and improved disclosure quality. Despite this, sustainability reporting quality does not have a significant effect on book–tax differences, and its mediating role in the relationship between board size and tax avoidance is rejected. Among control variables, only profitability ROA significantly affects tax avoidance, highlighting financial performance as the dominant agency-related driver of managerial tax decisions. Overall, the findings suggest that agency pressures arising from profitability outweigh governance and sustainability disclosure mechanisms in shaping corporate tax behavior.